Long-term change in alcohol-consumption status and variations in fibrinogen levels: the coronary artery risk development in young adults (CARDIA) study - Okwuosa, Tochi M (BMJ Publishing Group, 2013)
OBJECTIVE: To examine long-term associations between change in alcohol-consumption status and cessation of alcohol use, and fibrinogen levels in a large, young, biracial cohort. DESIGN: Analysis of covariance models were used to analyse participants within the Coronary Artery Risk Development in Young Adults Study (CARDIA) cohort who had fibrinogen and alcohol use data at year 7 (1992–1993; ages 25–37) and year 20 examinations. SETTING: 4 urban US cities. PATIENTS: 2520 men and women within the CARDIA cohort. MAIN OUTCOME MEASURES: 13-year changes in alcohol use related to changes in fibrinogen. RESULTS: Over 13 years, mean fibrinogen increased by 71 vs 70 mg/dL (p=NS) in black men (BM) versus white men (WM), and 78 vs 68 mg/dL (p<0.05) in black women (BW) versus white women (WW), respectively. Compared with never-drinkers, there were smaller longitudinal increases in fibrinogen for BM, BW and WW (but a larger increase in WM) who became or stayed drinkers, after multivariable adjustment. For BM, WM and WW, fibrinogen increased the most among persons who quit drinking over 13 years (p<0.001 for WM (fibrinogen increase=86.5 (7.1) (mean (SE))), compared with never-drinkers (fibrinogen increase=53.1 (5.4)). CONCLUSIONS: In this young cohort, compared with the participants who never drank, those who became/stayed drinkers had smaller increases, while those who quit drinking had the highest increase in fibrinogen over 13 years of follow-up. The results provide a novel insight into the mechanism for the established protective effect of moderate alcohol intake on cardiovascular disease outcomes.